Role of A.S. Aivazov in the Process of Primary Schools Reform in Crimea (1910s) - Ismail Kerimov (Крымское историческое обозрение)
After the death of I. Gasprinsky in 1914, the newspaper “Terdzhiman” was headed by the famous Crimean Tatar writer and publicist A.S. Aivazov. Under his leadership, a broad discussion was launched in the newspaper related to reforms in the field of national education in the primary grades of Crimea. The article makes an attempt to study the processes of reforms in education in the native language, showing a number of textbooks and teaching aids recommended by the general meeting of muallims (teachers) for use in the educational process in primary schools. Attention is drawn to the fact that it was these discussions that later acquired a national scale and led to the creation of the Mengli Giray Institute in Bakhchisaray in 1917, the first graduates of which, having received diplomas in 1920, joined the national teaching staff of Crimea.